Incidence, determinants and outcomes of ventilator associated pneumonia in medical intensive care unit: a prospective cohort study from South Western India - Rao, Shivaram; Bhat, Nitin; Bhat, Adarsha Gopadi Krishna; Hande, H. Manjunatha (International Journal of Research in Medical Sciences, 2021)
Background: Ventilators are being increasingly used in developing countries as a result of which complications like ventilator associated pneumonia is also increasing. Present study is being undertaken to evaluate the impact of risk factors and their changing trends for Ventilator associated pneumonia. Methods: A prospective observational study was conducted in mechanically ventilated patients of medical intensive care unit from October 2013 to April 2015. Results: In present study 166 patients receiving mechanical ventilation in a medical ICU were observed. Incidence of VAP in present study is 43.5 for 1000 days of mechanical ventilation. The risk factors that were significant in the study are organ failure (p=0.001), emergency intubation (p=0.001), reintubation (p=0.023) and COPD (p=0.026). The common organisms responsible for VAP were Acinetobacter (30%), Klebsiella pneumoniae (27.1%) and Pseudomonas aeruginosa (20%). The mortality was higher in VAP group (31.3%) compared to the non VAP group (15.7%). Conclusions: There is high incidence of VAP in the developing countries. The risk factors that were found to be associated with VAP in the present study were the presence of COPD, reintubation, organ failure and emergency intubation. VAP is associated with significantly increased duration of hospital stay, morbidity and mortality.